Critical Analysis of Multiculturalism in the Modern Islamic Education Curriculum - Samlawi; Rozak, M. Abdul; Abidin, Zaenal (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
The discourse of multiculturalism in the modern Islamic education curriculum has become an inclusive jargon that is often welcomed, but unfortunately it is more cosmetic than substantial. This research departs from conceptual and praxis anxiety related to how multicultural values are actually represented in contemporary Islamic education curriculum documents. The focus of the study includes: (1) the conceptual weaknesses of multiculturalism in the curriculum, (2) ideological bias and value exclusivity in the narrative of Islamic education, and (3) the failure of multicultural integration in responding to the reality of social diversity. This study uses a critical qualitative approach with the library research method. Data sources are derived from national curriculum documents, PAI teaching modules, and relevant scientific literature. Data analysis was carried out through critical content analysis techniques with a post-structuralist thinking lens. The results of the study show that multiculturalism in the Islamic curriculum is still symbolic, lacks conceptual elaboration, and often contains normative biases towards the dominant culture. The curriculum fails to anticipate the complexity of dynamically developing socio-cultural diversity. The conclusion of this study confirms the urgency of reconstructing the Islamic education curriculum with a multicultural basis that is more reflective, critical, and participatory